PENGARUH MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN DIVIDEN DENGAN LIKUIDITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN GROSIR YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Erliana, Elfira; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
Financial management is the most important management for a company. One of the functions of financial management is dividend policy. The purpose of this study was to analyze and examine the effect of working capital and sales growth on dividend policy with liquidity as an intervening variable in wholesale companies. This research is quantitative descriptive. The population of this study are wholesale companies listed on the IDX. The sampling technique in this research is purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that working capital has a significant positive effect on liquidity, sales growth has a significant positive effect on liquidity, working capital has a negative but not significant effect on dividend policy, sales growth has a significant positive effect on dividend policy, liquidity significant positive effect on dividend policy, working capital has a positive but not significant effect on dividend policy through liquidity, sales growth has a significant positive effect on dividend policy through liquidity.